Long Noncoding RNA LINC00839 Promotes the Malignant Progression of Osteosarcoma by Competitively Binding to MicroRNA-454-3p and Consequently Increasing c-Met Expression - Zhang Y (Cancer Management and Research, 2020)
Yang Zhang,1 Hai Guo,2 Li Ma,3 Xiaoyong Chen,1 Guangdong Chen4 1Department of Orthopedics, Shenzhen University General Hospital, Shenzhen 518055, People’s Republic of China; 2Department of Anesthesiology, First Affiliated Hospital of Xinjiang Medical University, Urumqi, Xinjiang, 830000, People’s Republic of China; 3Department of Emergency, General Hospital of Xinjiang Military Command of Chinese People’s Liberation Army, Urumqi, Xinjiang, 830000, People’s Republic of China; 4Department of Orthopedics, Cangzhou Center Hospital, Cangzhou, Hebei 061014, People’s Republic of ChinaCorrespondence: Yang Zhang Department of OrthopedicsShenzhen University General Hospital, 1098 Xueyuan Road, Nanshan District, Shenzhen 518055, People’s Republic of ChinaEmail zhangyang_szugh@126.comPurpose: This study was conducted to determine the expression and prognostic relevance of long intergenic non-protein coding RNA 839 (LINC00839) in osteosarcoma (OS) and to explore the detailed roles of LINC00839 in regulating OS cell activities and the mechanisms responsible for its cancer-promoting activity in OS.Methods: The expression of LINC00839 in OS tissues and cell lines was determined by quantitative reverse transcription–polymerase chain reaction. After LINC00839 knockdown, cell counting kit-8 assay, flow cytometric analysis, transwell migration and invasion assay, and in vivo tumor xenograft assay were used to detect its effects on cellular processes in OS. Bioinformatics analyses were conducted to predict the putative miRNAs that target LINC00839. RNA immunoprecipitation assay, luciferase reporter assay, Western blotting analysis, and rescue assays were conducted to establish a relationship among LINC00839, microRNA-454-3p (miR-454-3p), and cellular mesenchymal to epithelial transition factor (c-Met) in OS.Results: LINC00839 was upregulated in OS tissues and cell lines. OS patients characterized with high LINC00839 expression exhibited shorter overall survival than patients with low LINC00839 expression. LINC00839 knockdown caused a significant reduction in OS cell proliferation, migration, and invasion in vitro. Furthermore, LINC00839 depletion inhibited OS tumor growth in vivo and induced apoptosis. Mechanistically, LINC00839 functions as a competitive endogenous RNA in OS by sponging miR-454-3p. c-Met was confirmed as a direct target gene for miR-454-3p in OS cells and was positively regulated by LINC00839 by competitively binding to miR-454-3p.Conclusion: LINC00839 promoted the oncogenicity of OS by targeting the miR-454-3p/c-Met axis. The LINC00839/miR-454-3p/c-Met network may represent a potential target for OS therapy.Keywords: long intergenic non-protein coding RNA 839, ceRNA, therapeutic target